Acute Hypoxic and Refractory Respiratory Failure Induced by an Underlying PFO: An Unusual Case of Platypnea Orthodeoxia and Transient Complication after Transcatheter Closure - Carlos Salazar; Romeo A. Majano (Case Reports in Critical Care)
Platypnea orthodeoxia (PO) is an infrequent condition of dyspnea with hypoxemia, increased by adopting an upright position and is relieved in decubitus. This condition may occur in patients with hidden intracardiac shunts, usually across a persistent foramen ovale (PFO). The incidence of PFO in general population is quite common, around 27%; however, the concurrent presentation with PO, especially in acute refractory respiratory failure, is extremely rare. PFO closure in this setting is still the treatment of choice with significant improvement or complete resolution of symptoms after closure with an overall periprocedural complication in the first 24 hours of approximately less than 5%. A transient ST-segment elevation in the inferior leads is present in extremely rare occasions and most likely is induced by either an air embolism or a mechanically provoked spasm of coronary arteries. We report a case of an 83-year-old woman in acute hypoxic and refractory respiratory failure in whom PO was identified, most likely induced by a hidden PFO. The patient underwent percutaneous transcatheter closure and developed immediate chest pain, transient hemodynamic instability, and ST-segment elevation in the inferior leads; nevertheless, our patient recovered completely with rapid resolution of respiratory failure with no adverse clinical sequelae.